Speech Prosody 2018 2018
DOI: 10.21437/speechprosody.2018-139
|View full text |Cite
|
Sign up to set email alerts
|

The Perception-Production Link in Intonation: Evidence from German Learners of English

Abstract: Investigations of the link between the perception and production of prosody by language learners can inform theories of prosody perception and production, especially with regard to Second Language Acquisition (SLA), and for the implementation of prosody in Foreign Language Teaching (FLT). The perception and production of prosody in L2 speech are often analyzed separately, but the link between the two is rarely the focus of investigation [e.g. 1, 2].In a previous study [3], we analyzed the perception of prosody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…In summary, in comparing our two studies we have demonstrated that the Hong Kong learners attained the targets in production more than twice as much as in perception. This corroborates the finding for German learners of English in Puga et al (2018) and opposes the notion that perceptual capability necessarily precedes competence in production in L2 speech learning. While this may seem counter-intuitive, the fact that different mechanisms underlie perception and production may well explain what we have found.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In summary, in comparing our two studies we have demonstrated that the Hong Kong learners attained the targets in production more than twice as much as in perception. This corroborates the finding for German learners of English in Puga et al (2018) and opposes the notion that perceptual capability necessarily precedes competence in production in L2 speech learning. While this may seem counter-intuitive, the fact that different mechanisms underlie perception and production may well explain what we have found.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, we might suppose that the picture would be more complex in L2 acquisition of prosody, since intonational categories such as fall, rise and level pitch are universal, but the function of the categories is language-specific, not to mention the interplay of the linguistic and paralinguistic functions of intonation. Puga et al (2018) demonstrated -using the same procedure to test listeners' understanding of the suitability of tones in various contexts -that German learners of English performed significantly better in production than in what we are referring to as perception, i.e. at odds with the traditional assumptions of a perceptionproduction link.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…There are many studies focusing on CA of intonation in different languages (Deterding 2018;Eghlidi 2016;Esteve-Gibert et al 2018;Forsberg & Abelin 2018;Hayati 2005;Hellmuth 2018;Peters 2018;Puga et al 2018;Tsui & Tong 2018). There are several studies of the Persian language (Eghlidi 2016;Hayati 1996Hayati , 1998Hayati , 2005Soltani 2007;Yarmohammadi 2002) that focus specifically on contrasting the intonation patterns of Persian and English.…”
Section: Introductionmentioning
confidence: 99%